Large magnetic anisotropy in an OsIr dimer anchored in defective graphene - Navrátil, Jan; Błoński, Piotr; Otyepka, Michal (Nanotechnology, 2021)
Single-atom magnets represent the ultimate limit of magnetic data storage. The identification of substrates that anchor atom-sized magnets firmly and, thus, prevent their diffusion and large magnetic anisotropy has been at the centre of intense research efforts for a long time. Using density functional theory we show the binding of transition metal (TM) atoms in defect sites in the graphene lattice: single vacancy and double vacancy, both pristine and decorated by pyridinic nitrogen atoms, are energetically more favourable than away from the centre of defects, which could be used for engineering the position of TMs with atomic precision. Relativistic calculations revealed magnetic anisotropy energy (MAE) of ∼10 meV for Ir@NSV with an easy axis parallel to the graphene plane. MAE can be remarkably boosted to 50 meV for OsIr@NSV with the easy axis perpendicular to the graphene plane, which paves the way to the storage density of ∼490 Tb/inch2with the blocking temperature of 14 K assuming the relaxation time of 10 years. Magnetic anisotropy is discussed based on the relativistic electronic structures. The influence of an orbital-dependent on-site Coulomb repulsionUand a non-local correlation functional optB86b-vdW on MAE is also discussed.
Keywords: information storage; transition metal atoms and dimers; defective graphene; magnetic anisotropy energy